Electrical properties of Ag/p-Cu2NiSnS4 thin film Schottky diode. (September 2021) - Ghediya, Prashant R.; Palan, Yash M.; Bhangadiya, Drashti P.; Nakani, Ishrat I.; Chaudhuri, Tapas K.; Joshi, Kinjal; Sumesh, C.K.; Ray, Jaymin
Abstract: In this paper, we report the electrical properties of ITO/p-Cu2 NiSnS4 /Ag thin film Schottky diode fabricated by direct-ink-coating techniques. The Cu2 NiSnS4 (CNTS) films were dip-coated on substrates layer-by-layer from molecular ink synthesized from metal-thiourea complex dissolved in methanol. X-ray diffraction and Raman spectroscopy confirmed the formation of nanocrystalline cubic CNTS films. The optical band gaps of the films were found to reduce from 2.1 to 1.1 eV with increase in number of dip (thickness). The Current-Voltage (I-V) characteristics of Ag/p-Cu2 NiSnS4 junction was measured to ascertain rectification properties. Ideality factor, barrier height and saturation current density of typical Schottky diode is estimated to be 2.23, 0.33 eV and 0.013 mA/cm 2, respectively. Highlights: Electrical properties of Ag/p-Cu2 NiSnS4 thin film Schottky diode have been fabricated. Films are found to be pure cubic CNTS as revealed from XRD and Raman spectroscopy. Device parameters have been estimated from I-V characteristics. Higher η and Rs may be due to poor surface morphology.